Temperature dependence of inverted tunneling magnetoresistance in MGO-based magnetic tunnel junctions - COEY, JOHN MICHAEL DAVID; FENG, JIA-FENG (My University, 2010)
MgO-based magnetic tunnel junctions (MTJs) of the following main structure: Ir22Mn78 (10 nm) /Co90Fe10 (2 nm) /Ru (0.85 nm) /CoFeB (0.5t<2 nm) /MgO (2.5 nm) /CoFeB (3 nm) have been fabricated, with a thin CoFeB layer in the pinned synthetic antiferromagnetic CoFe/Ru/CoFeB stack. These MgO-based MTJs are of good barrier quality. Inverted tunneling magnetoresistance (TMR) has been observed for these MTJs, and the temperature (T) dependence of the inverted TMR are discussed in this work. The inverted TMR ratios are ?33% at room temperature (RT) and extrapolated to ?84% at 0 K for MTJs with t=1.0 nm, after annealing at 300 ?C. In this case, the TMR ratio at low temperature is more than double that of room temperature. Furthermore, the TMR ratio at low T is 3.8 times larger than that of 300 K for MTJs with t=0.5 nm, after annealing at 250 ?C. These results may be useful for spin electronic devices.
PUBLISHED
Keywords: Magnetic tunnel junction (MTJ); Tunneling magnetoresistance (TMR); Temperature dependence